2010
DOI: 10.1002/jemt.20855
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent imaging of reporter gene expression in the lungs of wildtype and model mice following the administration of PEG‐stabilized DNA nanoparticles

Abstract: DNA nanoparticles (DNPs) formed by compacting DNA with polyethyleneglycolylated poly-L-lysine are a nonviral vector shown to be safe and efficacious in animals and humans. To extend our capabilities of assessing the efficacy and duration of expression achieved by DNPs, we tested the utility of bioluminescent imaging (BLI) of transgene expression in wildtype and cystic fibrosis (CF) mouse models. We tested the effect of route of administration, mouse coat color, anesthesia, dose, and promoter sequence on the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…1A), in agreement with previous reports for CK 30 PEG-DNA nanoparticles [19, 27]. DNA nanoparticles exhibited a near neutral surface charge (−1.5 ± 3.9 mV), indicating the presence of PEG coating on the particle surface, and hydrodynamic diameter determined by dynamic light scattering was 89.0 ± 0.4 nm (PDI ~0.10).…”
Section: Resultssupporting
confidence: 91%
“…1A), in agreement with previous reports for CK 30 PEG-DNA nanoparticles [19, 27]. DNA nanoparticles exhibited a near neutral surface charge (−1.5 ± 3.9 mV), indicating the presence of PEG coating on the particle surface, and hydrodynamic diameter determined by dynamic light scattering was 89.0 ± 0.4 nm (PDI ~0.10).…”
Section: Resultssupporting
confidence: 91%
“…In the present study, the human beta-actin promoter resulted in sustained luciferase activity that increased over time (up to two weeks) in mice treated with PEG-CH 12 K 18 DNA nanoparticles or PEG-CK 30 DNA nanoparticles by oropharyngeal aspiration. The sustained luciferase activity mediated by DNA nanoparticles is consistent with a recent report by Ziady et al in which PEG-CK 30 DNA nanoparticles containing a luciferase plasmid driven by the ubiquitin B promoter resulted in sustained pulmonary expression in C57BL/6 mice that peaked within the first 14 days [46]. The authors also reported negligible luciferase activity in mice that received naked DNA, suggesting that compaction was necessary for efficient uptake and expression of DNA.…”
Section: Discussionsupporting
confidence: 89%
“…Such transient expression profiles are not ideal for the treatment of chronic lung disease, which requires sustained transgene expression at therapeutic levels. Alternatively, a number of eukaryotic promoters are capable of sustained pulmonary transgene expression, including the ubiquitin C [45, 47] and ubiquitin B [46, 48] promoters. In the present study, the human beta-actin promoter resulted in sustained luciferase activity that increased over time (up to two weeks) in mice treated with PEG-CH 12 K 18 DNA nanoparticles or PEG-CK 30 DNA nanoparticles by oropharyngeal aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…NPs have longer lung retention time compare to that of microparticles [92]. Ziady et al [93] also developed a DNA/polymer complex for bioluminescent imaging (BLI) of gene expression in the lung of wild type and cystic fibrosis mouse models. They found that BLI was an efficient imaging tool for the evaluation of gene expression mediated by these NPs and could be useful for clinical imaging applications in the future [93].…”
Section: Imaging/diagnostic Applicationsmentioning
confidence: 99%